2021
DOI: 10.1097/bpo.0000000000001877
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lateral Rotation Percentage and Rotational Deformity of the Elbow in Type 3 Supracondylar Humerus Fractures: A Biomechanical Study

Abstract: Background: Supracondylar humerus (SCH) fractures are the most common elbow fractures in children. Historically, displaced (Gartland type 3) SCH fractures have been treated with closed reduction and percutaneous pinning. Fluoroscopic imaging is used intraoperatively in order to assess adequate reduction of the fracture fragments before pinning. On lateral fluoroscopic and radiographic images, a lateral rotation percentage (LRP) can be estimated in order to assess rotational deformity. The purpose of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Therefore, it is highly likely that the provided angles do not apply to the majority of intraoperative and postoperative scenarios, because we frequently accept some displacement, have varying wire positions and frequently do not get true lateral views in the clinic. Therefore, we do not think that Berdis et al’s1 data can be used reliably for the majority of fractures to estimate the true degree of malrotation, with it being hitherto unknown if any malrotation/LRP can be accepted, without affecting cosmesis and/or function.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Therefore, it is highly likely that the provided angles do not apply to the majority of intraoperative and postoperative scenarios, because we frequently accept some displacement, have varying wire positions and frequently do not get true lateral views in the clinic. Therefore, we do not think that Berdis et al’s1 data can be used reliably for the majority of fractures to estimate the true degree of malrotation, with it being hitherto unknown if any malrotation/LRP can be accepted, without affecting cosmesis and/or function.…”
mentioning
confidence: 96%
“…Ryan et al4 reported that the AHL runs through the middle third of the capitellum in 100% of children 5 years of age and above but Berdis et al’s1 AHL runs through the front of the capitellum, indicating that the used bone model might not be an anatomic reproduction of a normal child’s humerus, which raises doubts about the reliability of the measured percentages.…”
mentioning
confidence: 98%
See 3 more Smart Citations